Plant breeder's rights - Evans, Philip; Haines, T. (School of Business Law, Curtin Business School, Curtin University of Technology, 2007)
In Australia, intellectual property protection is available for plants and plant material by way of standard patents, trade marks and plant breeder’s rights. The Plant Breeder’s Rights Act 1994 (Cth) (‘the PBR Act’) provides a legislative framework for the provision of a temporary monopoly over new plant varieties in order to encourage the development of such. This article examines the administrative process relating to the grant of Plant Breeder’s Rights (‘PBR’), criteria for protection, the scope of the rights, remedies for infringement and enforcement. Reference will also be made to relevant case law. The aim of this article is to raise the awareness of those involved in agriculture of the issues relating to PBR in order to assist in the commercialisation of new plant varieties.